Progress in the Applications of Photovoltaic Functional Crystals and Ceramics - Linghang Wang; Gang Xu (Crystals)
With the progression of mankind and the development of technology, great strides have been made regarding the application of inorganic crystalline materials in a number of fields such as high-energy and nuclear physics, environmental and safety inspection, the optoelectronics and communication fields, energy, and aerospace engineering, particularly the industrialization of photovoltaic and detector materials, which has brought mankind’s knowledge of natural disciplines to an all-time high [...]